(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2023)
Sufi orders have become a highly developed tribal organizational tool. We assume a sacred religious, political and worldly role, and it is the result of social influence that is considered a mechanism for materializing influence, especially towards the ruling authority and a means to control the tribes, by extinguishing their local conflicts with each other, and between the authority, which is what the rulers intended to do. At intervals, the method was used to control the tribe, so the method and the tribe carried out multiple tasks within their geographical scope, such as collection, markets, seasons, and the administration of the sanctuary. The store had nothing but to work to win the loyalty of these institutions or enter into a clash. Political factors, along with social and economic factors, contributed to the emergence of these institutions, as a result of many political, religious, social, and economic factors.